2020
DOI: 10.3389/fpubh.2020.611146
|View full text |Cite
|
Sign up to set email alerts
|

Underground Radiobiology: A Perspective at Gran Sasso National Laboratory

Abstract: Scientific community and institutions (e. g., ICRP) consider that the Linear No-Threshold (LNT) model, which extrapolates stochastic risk at low dose/low dose rate from the risk at moderate/high doses, provides a prudent basis for practical purposes of radiological protection. However, biological low dose/dose rate responses that challenge the LNT model have been highlighted and important dowels came from radiobiology studies conducted in Deep Underground Laboratories (DULs). These extreme ultra-low radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Many studies reported that people in high level background radiation area above 10 mSv/year showed no health risks for cancers or life-shortening, compared to the residents in other areas (Hendry et al, 2009). Furthermore, underground biology studies in Deep Underground Laboratories (DULs) characterized by substantial reduction of the exposure to environmental radiation background showed that background level of radiation could influence the sustaining the life of organisms, modulating the expression of several genes involved in protein metabolism and stress response (Esposito et al, 2020;Castillo et al).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…Many studies reported that people in high level background radiation area above 10 mSv/year showed no health risks for cancers or life-shortening, compared to the residents in other areas (Hendry et al, 2009). Furthermore, underground biology studies in Deep Underground Laboratories (DULs) characterized by substantial reduction of the exposure to environmental radiation background showed that background level of radiation could influence the sustaining the life of organisms, modulating the expression of several genes involved in protein metabolism and stress response (Esposito et al, 2020;Castillo et al).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…The Gran Sasso National Laboratory (LNGS) at Assergi (L’Aquila, Italy) is one of the largest DULs in the world, hosting the largest number of biological experiments performed to date. Due to the 1400-m coverage of dolomitic rocks poor in uranium and thorium, at LNGS the flux of cosmic rays is considered negligible as it is reduced by approximately 6 orders of magnitude, while the neutron flux is 1000 times reduced with respect to the external environment [ 12 , 13 ]. The setting up of two dedicated facilities, namely, PULEX and COSMIC SILENCE for cell culture and animal housing, respectively, allowed researchers to gather several pieces of evidence on the influence of the deprivation of a natural level of environmental radiation in different model systems [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the 1400-m coverage of dolomitic rocks poor in uranium and thorium, at LNGS the flux of cosmic rays is considered negligible as it is reduced by approximately 6 orders of magnitude, while the neutron flux is 1000 times reduced with respect to the external environment [ 12 , 13 ]. The setting up of two dedicated facilities, namely, PULEX and COSMIC SILENCE for cell culture and animal housing, respectively, allowed researchers to gather several pieces of evidence on the influence of the deprivation of a natural level of environmental radiation in different model systems [ 12 , 14 ]. In particular, a few years ago, we launched the FLYINGLOW project that aimed to determine whether the LNGS’s underground environment could affect the growth and development of the well-established model organism, Drosophila melanogaster .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth rate inhibition, increased sensitivity to radiation, delayed recovery after return to natural background conditions, alteration in expression of several genes concerned with ribosomal proteins, membrane transport, respiration, reparation and antioxidant regulation for increased ROS removal were observed in experiments on mammalian cell cultures (TK6, V79, M10, L5178Y, FD-LSC-1) and unicellular organisms ( Paramecium tetraurelia , Synechococcus lividus , Shewanella oneidensis , Deinococcus radiodiodurans , Saccharomyces cerevisiae ) [ 11 , 12 , 14 , 17 , 18 , 24 , 25 ]. The first multicellular organism used for determination of the effects of low-radiation background was the fruit fly in projects FLYINGLOW and RENOIR [ 20 , 26 ]. These experiments established that D .…”
Section: Introductionmentioning
confidence: 99%